2017
DOI: 10.1136/bmjopen-2016-014912
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non-pharmacological treatments for major depressive disorder: review of systematic reviews

Abstract: ObjectivesThis study aims to summarise the evidence on more than 140 pharmacological and non-pharmacological treatment options for major depressive disorder (MDD) and to evaluate the confidence that patients and clinicians can have in the underlying science about their effects.DesignThis is a review of systematic reviews.Data sourcesThis study used MEDLINE, Embase, Cochrane Library, PsycINFO and Epistemonikos from 2011 up to February 2017 for systematic reviews of randomised controlled trials in adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 51 publications
5
107
0
5
Order By: Relevance
“…More reliable than differences in subjective rating scales are objective outcomes such as premature treatment termination. Several meta-analyses did not detect a noticeable difference between antidepressant and placebo arms with respect to overall dropout rates in short-term RCT ( 51 53 ). Assuming that patients prematurely terminate a free treatment only if they perceived it as useless or even harmful ( 54 ), these findings indicate that the average patient experiences no clear benefits from antidepressants.…”
Section: Acute Therapymentioning
confidence: 99%
“…More reliable than differences in subjective rating scales are objective outcomes such as premature treatment termination. Several meta-analyses did not detect a noticeable difference between antidepressant and placebo arms with respect to overall dropout rates in short-term RCT ( 51 53 ). Assuming that patients prematurely terminate a free treatment only if they perceived it as useless or even harmful ( 54 ), these findings indicate that the average patient experiences no clear benefits from antidepressants.…”
Section: Acute Therapymentioning
confidence: 99%
“…The first-line treatment for depression may include either a selective serotonin reuptake inhibitor (SSRI) or a tricyclic antidepressant (TCA) [ 4 ]. Although several antidepressant formulations are available in the market for the therapeutic management of depression, the majority of them have a wide range of side effects [ 5 ]. Therefore, the use of herbal extracts in their crude from or a semi-purified form is gaining ground among clinicians as well as patients as an alternative therapy for depressive disorders [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A systematic review published in 2017 revealed that in contrast to pharmacological treatment, most non-pharmacological interventions for treating patients with major depressive disorder are not evidence-based. 19 On the other hand, exercise therapy, bibliotherapy, CBT, short-term psychodynamic supportive psychotherapy, and interpersonal psychotherapy (IPT) are considered valid non-pharmacological treatments for adult patients with mild or moderate depression in Korea. 20 Anxiety disorders involve excessive fear and are irrational.…”
Section: Introductionmentioning
confidence: 99%